An investigation of tourists motivational factors of using health and spa facilities in five-star resorts in Kota Kinabalu, Sabah - Inoormaziah Azman (2011)
The changing needs in the population and the growing health-concern that is germinated in today’s society have led to healthier lifestyle practices. People consume healthy and balanced diets and participate in various kinds of activities from mainstream exercises to frequent visits to sport and wellness centers. Likewise, the tourists seek to participate in activities that improve their health and well-being, including visits to health and spa centers at a particular holiday destination. It argues that a deep understanding of consumer profiles and their key motivations within this context is vital in order to sustain the growth of health and spa tourism business. This research seeks to understand the health and spa tourists’ motivation that are grounded in their own words during their visits to health and spa service centers in Sabah, Malaysia. The main objectives are to describe the perceptions and identify the key motivations of health and spa among international tourists, and explain their travel behaviors in health and spa tourism by extending the push-pull motivation theory that focuses on the individual’s psychological factors (motivation, perception and attitude towards health and spa) and the destination’s (Sabah’s) health and spa attributes. Data collection was conducted using in-depth interviews with 21 foreign tourists who had utilized health and spa services in Sabah, Malaysia. The finding reveals that the health and spa tourists’ motivations are mainly attributed to the push factors, which related to the psychological needs of the tourists including escape, rest and relaxation. The pull factors (health and spa attributes) mainly as the key attributes of the whole spa experiences, in addition to key attractiveness to the tourists to visit health and spa, which including professionalism, spa treatments and the physical environment of the spa establishment. This contributes to a better understanding of health and spa in terms of push (health and spa tourists’ key motivation) and pulls (key attractiveness of local health and spa) factors. It benefits the health and spa service providers in terms of developing appropriate marketing strategies that concentrate on fulfilling the psychological needs of the tourists, and enhanced tourist satisfaction by paying attention to the key attributes that eventually contribute to a more remarkable spa experiences. However, due to the nature of the qualitative study and the type of respondent (foreign tourists) of this research, it limits the generalizability of the research findings. It suggests a comparative work in a similar context in different locations and countries would prove beneficial for the possible validation of the findings. Additionally, the generalization of the research findings can be extended through further research such as the use of these motivational factors as variables in the quantitative approach in other context of health and spa tourism – health and spa tourists’ satisfaction, spa treatment preferences, or perceptions and expectations.